Role of Retailing and Growth of Hypermarkets in India - Venkateswatan, N.; Mahalakshmi, V. (Indian Journal of Marketing, 2009)
Liberalization of the economy in the nineties and the entry of large players in the retail business have brought the retail industry into spotlight. Big players and national retail chains are changing the rules of the game. After supermarkets, departmental stores and convenience stores, Indian retail has seen the concept of hypermarkets coming of age. The hypermarkets are not new to the western countries. Players like Wal-mart, Metro have established hypermarkets in many countries. In India, the hypermarket concept is in its nascent stage. Retailers like Pantaloons and RPG have started hypermarket operations and they are having plans to expand aggressively to all the regions of India. A large number of international retailers have evinced interest in India, despite the absence of favorable government policy for foreign players.